Evaluation of the immunogenicity of vaccine candidates developed using a baculovirus surface display system for Crimean-Congo hemorrhagic fever virus in mice - Zhang, Gang; Wang, Pu; Jiang, Lingling; Wang, Sheng; Zhang, Sinong; Li, Yong (Frontiers in Microbiology, 2023)
Crimean-Congo hemorrhagic fever (CCHF), which has a fatality rate of 20-30%, is widely prevalent in several regions in Asia, Europe, and Africa and has spread to a wider range of areas in recent years. At present, there is a lack of safe and effective vaccines for the prevention of CCHF. In this study, we prepared three vaccine candidates, rvAc-Gn, rvAc-Np, and rvAc-Gn-Np, that encoded the CCHF virus (CCHFV) glycoprotein Gn and the nucleocapsid protein (Np) on the surface of baculovirus using an insect baculovirus vector expression system (BVES) and evaluated their immunogenicity in BALB/c mice. The experimental results showed that both CCHFV Gn and Np were expressed by the respective recombinant baculoviruses and anchored to the viral envelope. BALB/c mice were immunized, and all three recombinant baculoviruses showed significant humoral immunity. At the cellular level, the level of immunity in the rvAc-Gn group was significantly higher than that in the rvAc-Np and rvAc-Gn-Np groups, and the rvAc-Gn-Np coexpression group exhibited the lowest level of cellular immunity. In conclusion, the strategy of coexpressing Gn and Np in the baculovirus surface display system did not result in improvements in immunogenicity, whereas the recombinant baculovirus displaying Gn alone could induce significant humoral and cellular immunity in mice, indicating that rvAc-Gn has potential as a CCHF vaccine candidate. This study thus provides new ideas for the development of a CCHF baculovirus vaccine.